2022
DOI: 10.3390/brainsci12111548
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Peripheral Magnetic Stimulation Combined with Motor Imagery Changes Resting-State EEG Activity: A Randomized Controlled Trial

Abstract: Repetitive peripheral magnetic stimulation is a novel non-invasive technique for applying repetitive magnetic stimulation to the peripheral nerves and muscles. Contrarily, a person imagines that he/she is exercising during motor imagery. Resting-state electroencephalography can evaluate the ability of motor imagery; however, the effects of motor imagery and repetitive peripheral magnetic stimulation on resting-state electroencephalography are unknown. We examined the effects of motor imagery and repetitive per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Repeated MI improves the vividness of MI (Iso et al, 2021). Nevertheless, studies of MI with simultaneous action observation (Ono et al, 2013) and repetitive peripheral magnetic stimulation (Sawai et al, 2022) reported no difference in the improvement of MI vividness between groups compared to that in MI alone. Similarly, in this study, there was no difference between the NFB and the NFB + tDCS groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Repeated MI improves the vividness of MI (Iso et al, 2021). Nevertheless, studies of MI with simultaneous action observation (Ono et al, 2013) and repetitive peripheral magnetic stimulation (Sawai et al, 2022) reported no difference in the improvement of MI vividness between groups compared to that in MI alone. Similarly, in this study, there was no difference between the NFB and the NFB + tDCS groups.…”
Section: Discussionmentioning
confidence: 99%
“…Participants rated the vividness by making a mark on a 100-mm horizontal line, where 0 equaled "not at all" and 100 equaled "very vivid image." MI vividness correlates with cortical excitability (Moriuchi et al, 2020) and has been used in MI studies involving healthy participants as a simple and subjective MI assessment (Iso et al, 2021;Sawai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motor imagery is known to improve performance [29] and has a motor-learning effect [30] even when the participant does not actually exercise. In addition, motor imagery has been supported from a neurological aspect, as there are areas where brain activity similar to that of actual exercise is observed [31], and resting EEG is altered by motor imagery [32]. On the basis of these background characteristics, motor imagery has been used in sports training for athletes [33] and in rehabilitation for stroke patients [34,35].…”
Section: Motor Imagery-based Neurofeedbackmentioning
confidence: 99%